Perceptions of Special School Nurses in Hong Kong During the COVID-19 Pandemic - Yip, Ka-Huen; YIP, Yuk-Chiu; TSUI, Wai-King (Advances in Nursing & Midwifery, 2021)
Abstract Introduction: The coronavirus (COVID-19) pandemic is a global public health crisis that started in 2020. Although health authorities believe that reducing social contact between students is necessary to protect students’ health, there is limited research on the lived experiences of school nurses caring for children and adolescents with intellectual disabilities (ID) in special schools during the COVID-19 pandemic. The aim of this study was to explore the experiences of school nurses caring for children and adolescents with ID in Hong Kong. Methods: This study used a phenomenological research design focused on experiences, events, and occurrences. Nine school nurses working in special schools in Hong Kong shared their lived experiences of caring for students with ID during the COVID-19 pandemic. Transcripts were analyzed according to the steps in Colaizzi’s method to understand and accurately describe the experiences of school nurses. Results: The role of school nurses during the COVID-19 pandemic was complex and multi-dimensional. Three themes emerged from the interview data: (1) the unpredictable and uncertain situation of COVID-19, (2) the extreme emotions experienced while caring for students during the outbreak of COVID-19, and (3) the inevitability of committing nursing errors during the outbreak of COVID-19. Conclusions: This study provided first-hand insights into nurses’ experiences in caring for students with special health needs during the COVID-19 pandemic. The findings indicated that continuous support from school organizations is needed to enable school nurses to care for students and their parents during a public health crisis, and to help school nurses to cope with unpredictable situations.